2023
DOI: 10.1038/s41598-023-28520-4
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of the incidence of severe adverse events among recipients of chiropractic spinal manipulative therapy

Abstract: This study examined the incidence and severity of adverse events (AEs) of patients receiving chiropractic spinal manipulative therapy (SMT), with the hypothesis that < 1 per 100,000 SMT sessions results in a grade ≥ 3 (severe) AE. A secondary objective was to examine independent predictors of grade ≥ 3 AEs. We identified patients with SMT-related AEs from January 2017 through August 2022 across 30 chiropractic clinics in Hong Kong. AE data were extracted from a complaint log, including solicited patient sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 49 publications
0
45
0
Order By: Relevance
“…However, as the previous case showed improvement after chiropractic spinal manipulation (i.e., a manual therapy applied to the spine), the authors suggested that this treatment restored the function of involved joints and muscles [13]. In contrast, spinal manipulation was contraindicated in the current case due to the presence of spinal metastasis [8]. Instead, the priority was to refer the patient for oncologic management.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…However, as the previous case showed improvement after chiropractic spinal manipulation (i.e., a manual therapy applied to the spine), the authors suggested that this treatment restored the function of involved joints and muscles [13]. In contrast, spinal manipulation was contraindicated in the current case due to the presence of spinal metastasis [8]. Instead, the priority was to refer the patient for oncologic management.…”
Section: Discussionmentioning
confidence: 76%
“…As such, chiropractors may occasionally be faced with unusual case presentations which could be harbingers of serious underlying systemic disease [7]. Therefore, early identification of metastasis is imperative not only to facilitate oncologic care but also to avoid any chiropractic treatment-related fractures among patients with compromised bone integrity [8]. Despite it being important for chiropractors to identify metastasis, there is limited research on this topic [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike traditional medical treatment utilizing medications and modalities such as electrical stimulation and ultrasound, an alternative conservative option was presented because the patient, a professional athlete, desired to refrain from taking medications. Given that the patient experienced pain alleviation soon after the therapy and adverse events related to chiropractic treatment are very rare [ 10 ], we hypothesized that the combination of adjacent joint manipulation and soft tissue mobilization contributed to his quick recovery. We believe that the relief achieved through joint manipulation was due to the restoration of normal joint movement in the periphery, which may have been impeded by injury or damage.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, spinal infections represent a contraindication to common chiropractic treatments such as spinal manipulation [ 4 ]. While spinal manipulation is generally safe, it may fracture already weakened bone [ 5 ]. Despite the importance of this topic, presentations of spinal infection in the chiropractic office are seldom reported in the literature [ 4 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%